Calcium channels and transporters: Roles in response to biotic and abiotic stresses - Park, Chang-Jin; Shin, Ryoung (Frontiers in Plant Science, 2022)
Calcium (Ca2+) serves as a ubiquitous second messenger by mediating various signaling pathways and responding to numerous environmental conditions in eukaryotes. Therefore, plant cells have developed complex mechanisms of Ca2+ communication across the membrane, receiving the message from their surroundings and transducing the information into cells and organelles. A wide range of biotic and abiotic stresses cause the increase of [Ca2+]cyt as a result of the Ca2+ influx permitted by membrane-localized Ca2+ permeable cation channels such as CYCLIC NUCLEOTIDE-GATE CHANNELs (CNGCs), and voltage-dependent HYPERPOLARIZATION-ACTIVATED CALCIUM2+ PERMEABLE CHANNELs (HACCs), as well as GLUTAMATE RECEPTOR-LIKE RECEPTORs (GLRs) and TWO-PORE CHANNELs (TPCs). Recently, resistosomes formed by some NUCLEOTIDE-BINDING LEUCINE-RICH REPEAT RECEPTORs (NLRs), are also proposed as a new type of Ca2+ permeable cation channels. On the contrary, some Ca2+ transporting membrane proteins, mainly Ca2+-ATPase and Ca2+/H+ exchangers, are involved in Ca2+ efflux for removal of the excessive [Ca2+]cyt in order to maintain the Ca2+ homeostasis in cells. The Ca2+ efflux mechanisms mediate the wide ranges of cellular activities responding to external and internal stimuli. In this review, we will summarize and discuss the recent discoveries of various membrane proteins involved in Ca2+ influx and efflux which play an essential role in fine-tuning the processing of information for plant responses to abiotic and biotic stresses.